Risk of Fall among Elderly People Residing in an Urban Municipality of Eastern Nepal - Limbu, Pramila; Chalise, Gita Dhakal; Shrestha, Sarala (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Falls are a major public health issue and a leading cause of morbidity and mortality among older people. Majority of falls are preventable and injuries related to it can be reduced through early identification of risk factors and timely introduction of appropriate intervention. Therefore, the purpose of this study was to find out the risk of falls and its associated factors among elderly people. Methods: A descriptive cross-sectional design was used. Using non-probability purposive sampling technique, a total of 103 elderly people aged 70 - 79 years were selected. Data were collected from the respondents by using pretested semi-structured interview schedule and “Time Up and Go” test at their homes. Data were analyzed by using descriptive and inferential statistics. Results: Out of 103 respondents, 52.4% reported a history of falls within 12 months, 68% had history of chronic disease and 65% were taking medicine. Vision problem was reported by 74.8%. “Time Up and Go” test revealed that the majority (61.2%) were at high risk of fall. The risk was significantly associated with age (p = 0.001), educational status (p = 0.019) and history of fall within 12 months (p = 0.001). Conclusion: Study concludes that elderly people aged 70 to 79 tend to be generally at high risk of fall. Age, educational status and history of fall within 12 months influence the risk of fall among elderly people.